Surgery offers survival advantage over radiotherapy in patients who are 80 years and older with Stage I and II NSCLC: A retrospective cohort study of 7,045 patients - Guo, Qiang; Hu, Sheng; Ye, Jiayue; Su, Lang; Wang, Silin; Zhang, Deyuan; Zhang, Yang; Qiu, Shengyu; Zhu, Lingxiao; Ruan, Liancheng; Wan, Bingen; Zou, Sheng; et al. (Frontiers in Surgery, 2022)
Abstract Objective: Elderly people are less likely than younger patients to undergo curative surgery for early-stage lung cancer because of the greater risk of surgery and postoperative complications. We investigated the relationship between treatment modality and the risk of all-cause and lung cancer-specific mortality to compare the efficacy of surgical treatment with radiotherapy in patients with stage I and II non-small cell lung cancer (NSCLC) who were  80 years old. Methods: We extracted data from the most recent Surveillance, Epidemiology, and End Results 9 registry study database (2010¬-2017). We mainly selected patients with stage I and II NSCLC who were  80 years old, and after screening, 7045 cases were selected for our study. We used univariate analysis, stratified analysis, and multiple regression equation analysis to examine all-cause mortality and lung cancer-specific mortality in different treatment modalities. The overall and stratified populations' survival curves were plotted using the Kaplan–Meier method. The competing risk regression method of Fine and Gray was used to estimate mortality specific to lung cancer. Results: In the fully adjusted model, all-cause mortality was 1.97 times higher in the radiotherapy-only group (hazard ration (HR) = 1.97, 95% confidence interval (CI) = 1.81–2.14, p < 0.0001) than in the surgery-only group. The lung cancer-specific mortality rate was 1.22 times higher in the radiotherapy-only group (HR = 1.22, 95% CI = 1.13–1.32, p < 0.0001) than in the surgery-only group. The median overall survival (OS) in the surgery-only, radiation therapy only, surgery plus radiation therapy, and no-treatment groups were 58 months, 31 months, 36 months, and 10 months, respectively. Median lung cancer-specific survival was 61 months, 32 months, 38 months, and 11 months, respectively. The surgery-only group had the highest 1-year OS (0.8679,95% CI = 0.8537–0.8824) and 5-year OS (0.4873, 95% CI = 0.4632–0.5126). Conclusions: Surgery had a higher overall and lung cancer-specific survival rate than radiotherapy and no treatment in the elderly early-stage NSCLC population. For patients with stage I and stage II NSCLC at advanced ages, surgical treatment might have a greater potential survival benefit.